Pengaruh Opini Audit, Financial Distress, dan Pertumbuhan Perusahaan Klien Terhadap Auditor Switching (Studi pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Tahun 2010-2014) - Faradila, Yuka (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2016)
The research examines the effect of audit opinion, financial distress, and growth of the clientâs company on auditor switching among manufactures companies listed in Indonesia Stock Exchange in 2010-2014. Secondary data were sourced from the financial statements, published by the capital market reference center at the Indonesia Stock Exchange.The research type used in this research is hypothesis testing, by using purposive sampling method. There are 30 samples of the data that become the object to be researched. This research uses logistic regression analysis to test the hypothesis.The results of this research show that audit opinion, financial distress,and growth of the clientâs company have effect on auditor switching. Partially the research shows that (1) audit opinion significantly influences auditor switching (2) financial distress do not affects auditor switching, and (3) growth of the company significantly influences auditor switching.